A Presentation of World Musical Styles of the Western Boehm Flute - Lueck, Amanda (East Carolina University, 2017)
Long prior to planning my senior recital I mentioned to my flute professor, who would become my mentor for the Senior Honors Project, that I was interested in the music of other cultures. She mentioned the term 'ethnomusicology' to me, but at the time I wasn't familiar with that field. This became the central point upon which I built my project. My goal was to introduce to the audience music that did not meet their expectations of Western flute repertoire, and to challenge their preconceptions about flute music.
Keywords: Music; flute; culture